Sejarah filsafat barat : dan kaitannya dengan kondisi sosio-politik dari zaman kuno hingga sekarang - Jatmiko, Sigit (Pustaka Pelajar, 2002)
Judul asli: History of wester philosophy and its connection with political and social circumstances from the earliest times to the present day